Carbon Footprint Estimation for Pole and Line Fishing Vessel According to Its Operation Mode -Study Case at Papua Fisheries- - Wardhana, Ede Mehta; Pitana, Trika; Suryanto, Ir. (Journal of Ocean, Mechanical and Aerospace -science and engineering-, 2016)
Carbon Footprint is one of the newest issue that people are concerned about especially on Fisheries business in Indonesia. The ships are growing bigger in terms of number and it makes the environment issue also became more concern for the people’s life and wellbeing. In this experiment, those issues will be analyzed with Carbon Footprint on Fishing Ships in Sorong. This experiment will be analyzed using mathematical analysis based on literature that used in order to get the emission factor and also to calculate the carbon footprint emission on site. Those calculations will be used as basic logic calculation using the emission factor multiplied by fuel consumption. The purpose of this experiment is to understanding the Mode of the operation of the fishing ships in order to calculate the emissions. This experiment purpose is to get estimation of the amount of exhaust gas from fishing ships emission and also to get the constant value for each fuel that used for the fishing ships on the experiment site.